Police interviewers’ experiences of the Tactical Interview Model (TIM): an exploratory study of suspect interviewing in Norway - Risan, Patrick (Psychology, crime & law, 2025)
The purpose of the study was to qualitatively explore how police investigators in Norway experience interviewing suspects. Specifically, we sought to investigate the relationship between theory (the Tactical Interview Model) and practice concerning how police interviewers establish the interviewee’s account and disclose potential evidence-related information. To explore processes relevant to the research objective, four focus group interviews of police interviewers were conducted (n = 29). The data was analysed using a thematic analysis which resulted in four main themes: (1) Planning and preparing: considering potentially evidence-relevant information – Its possible value, alternative explanations, and influence on the interview process, (2) Establishing rapport and balancing dilemmas: Providing sufficient information without affecting the interviewee’s account, (3) Exploring the interviewee’s account through questioning and ‘closing doors’, and (4) Challenge through clarification: disclosure of potential evidence-related information and adapting to the interviewee. The findings are discussed in relation to the Tactical Interview Model. Implications for practice and future directions are presented.